2023
DOI: 10.1055/s-0043-1761466
|View full text |Cite
|
Sign up to set email alerts
|

Update of the Brazilian consensus recommendations on Duchenne muscular dystrophy

Abstract: In the last few decades, there have been considerable improvements in the diagnosis and care of Duchenne muscular dystrophy (DMD), the most common childhood muscular dystrophy. International guidelines have been published and recently reviewed. A group of Brazilian experts has developed a standard of care based on a literature review with evidence-based graded recommendations in a two-part publication. Implementing best practice management has helped change the natural history of this chronic progressive disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Nonetheless, a multidisciplinary approach targeting the symptoms of DMD can change the natural course of the disease. Glucocorticosteroids, such as deflazacort or prednisone, are the current standard of care treatment for DMD patients (Araujo 2023). 84 Genetic therapies that act by regulating the expression of DMD or administering a transcript capable of encoding a smaller but still functional dystrophin have been the most promising therapies.…”
Section: Gene-based Therapies For Duchenne Muscular Dystrophymentioning
confidence: 99%
“…Nonetheless, a multidisciplinary approach targeting the symptoms of DMD can change the natural course of the disease. Glucocorticosteroids, such as deflazacort or prednisone, are the current standard of care treatment for DMD patients (Araujo 2023). 84 Genetic therapies that act by regulating the expression of DMD or administering a transcript capable of encoding a smaller but still functional dystrophin have been the most promising therapies.…”
Section: Gene-based Therapies For Duchenne Muscular Dystrophymentioning
confidence: 99%
“…Given the limitations of the studies reviewed, such as confounding by indication, small sample size, and lack of longitudinal follow-up, the authors concluded that the optimal timing of clinical interventions, including glucocorticoids and ataluren, in DMD is still unknown and that further research is needed [ 166 ]. Expert recommendations slightly differ, yet generally lean toward advocating steroid trials for children aged 2 to 5 [ 174–177 ]. Notably, in June this year, delandistrogene moxeparvovec-rokl (SRP-9001) gained FDA approval to treat ambulatory pediatric patients aged 4 to 5 with certain DMD gene mutations.…”
Section: Neuromuscular Diseases With Evidence Supporting Benefits Of ...mentioning
confidence: 99%